The history and growth of the South African Press from the time of the arrival of the first Press until the present day; a survey of the Bantu Press, of legislation affecting the Press, of the relationship between the Press and certain institutions and a prophecy as to the probable lines of development in the future - Brookes, E.H. (University of Pretoria, 2013)
Dissertation (MA)--University of Pretoria, 2012.